Aligning extracurricular school activities with physical literacy: pilot evaluation through self-study of practice - Schmittwilken, Louisa; Harding-Kuriger, Jodi; Carl, Johannes (Frontiers in Sports and Active Living, 2024)
Introduction Although several important documents of education and health promotion on the international level favor practices geared toward physical literacy (PL), not all countries have yet gained experience with this holistic concept. Therefore, numerous stakeholders and practitioners who intend to align their interventional activities with PL will soon face the situation that there are no recommendations for their specific culture and language for how to design such programs. Given that such recommendations are also lacking for Germany, the goal of the present study within the uncontrolled pilot cycles of the PLACE study was (a) to describe the process of a female pedagogue (27 years old, previously unexperienced with PL) initially familiarizing herself with the PL concept and its implementation opportunities for the school setting, and (b) to retrace the process of developing and refining a PL-driven intervention for extracurricular physical education (60–90 min) of children in grades three and four at primary schools in Bremen. Methods Adopting a self-study design, this endeavor emphasized continuous reflexivity involving: (a) session protocols; (b) biweekly discussions with another coach; (c) weekly discussions between scientists and stakeholders of youth development (“multi-perspective panel”); (d) weekly observations and impressions during field work; and (e) summative group interviews with children (n = 17, age range: 8–9 years, 17.6% boys). Written documents underwent qualitative content analysis with inductively generated categories. Results Despite explicit links between the theoretical PL domains and the intervention content, the character of how PL informed the intervention level was dominated by the stance and atmosphere implemented by the deliverer (e.g., participatory attitude, open mindset). Accordingly, the team revised the intervention primarily on the levels of organization (temporal schedule and sequences), instruction, and materials. After initial stages of didactically “surviving” within classes, the deliverer could increasingly integrate tasks of cognitive engagement and provide choice for students enabling individual autonomy for nurturing a person-centered approach. Discussion This study encourages teachers and stakeholders of physical education to seek exchange with scholars or other practitioners while simultaneously demonstrating patience in comprehensively internalizing PL and efficiently translating the concept into routines in line with individual's quality standards.